2011
DOI: 10.2217/fmb.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Treating Mycobacterium ulcerans disease (Buruli ulcer): from surgery to antibiotics, is the pill mightier than the knife?

Abstract: Until 2004, the skin disease known as Buruli ulcer, caused by Mycobacterium ulcerans, could only be treated by surgery and skin grafting. Although this worked reasonably well on early lesions typically found in patients in Australia, the strategy was usually impractical on large lesions resulting from diagnostic delay in patients in rural West Africa. Based on promising preclinical studies, treatment trials in West Africa have shown that a combination of rifampin and streptomycin administered daily for 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 94 publications
1
51
0
Order By: Relevance
“…Firstly, the mouse was too small to facilitate a proper clinical evaluation of the ulcers. Secondly, the ulcers were short-lived and progressed rapidly to necrosis, resulting in the destruction of the limb (Addo et al, 2005), as also observed later on by Converse et al (2011). These findings support the assertion that better BU animal models need to be found.…”
Section: The Mouse Footpad Modelsupporting
confidence: 61%
“…Firstly, the mouse was too small to facilitate a proper clinical evaluation of the ulcers. Secondly, the ulcers were short-lived and progressed rapidly to necrosis, resulting in the destruction of the limb (Addo et al, 2005), as also observed later on by Converse et al (2011). These findings support the assertion that better BU animal models need to be found.…”
Section: The Mouse Footpad Modelsupporting
confidence: 61%
“…1 The WHO recommended first-line treatment of BU is daily injection with streptomycin (SR) and oral rifampicin for 8 weeks, and if necessary, surgery either to improve healing and/or to correct deformities. 1,5,6 The efficacy of this treatment regimen has been confirmed in several studies. [7][8][9] Active lesions present with large focal clusters of extracellular acid-fast bacilli (AFB) and only minor leukocyte infiltration.…”
Section: Introductionmentioning
confidence: 81%
“…Currently, Buruli ulcer is managed on a regimen of streptomycin and rifampicin for an eight-week period as recommended by the WHO [9, 10]. This was a shift from an initial wide surgical excision of the infected tissue, followed by skin grafting [11, 12]. In severe cases, patients are treated with antibiotics in addition to surgery.…”
Section: Introductionmentioning
confidence: 99%